An approach to secularism from the perspective of Charles Taylor. Breaking down the key ideas of A Secular Age, volume I - Sánchez Berríos, Jesús Eleazar (2022)
Although most thinkers agree that we live in secular societies, they do not always share the same understanding of this concept. Since the philosopher Charles Taylor has exemplarily investigated the subject of secularity in his writings, I will comment on the fundamental ideas of the first volume of his book A Secular Age (2007). The three central ideas recognized in this book are studied in the three respective sections of this paper: 1) the four meanings of secularity, 2) the titanic change in Western society and 3) the historical itinerary of such titanic change from the transcendent to the immanent.